Penerapan Sekuen 3d Sagital Pd Cube Fs Dalam Pemeriksaan Mri Lutut Kasus Susp Ruptur Acl Dan Meniscus Injury - Adipranata, I Made Darma; Juliantara , I Putu Eka (Syntax Corporation, 2025)
MRI of knee is a key imaging modality for detecting soft tissue injuries such as anterior cruciate ligament (ACL) rupture and meniscal tears. The 3D SAGITAL PD CUBE FS sequence offers volumetric image acquisition with isotropic voxels and multiplanar reconstruction capabilities without significant image quality loss. This study was conducted at the radiology installation of Hospital in East Java. A descriptive qualitative method was employed through direct observation, interviews with radiologists and radiographer and documentation of knee MRI result. The findings demonstrated that the 3D SAGITAL PD CUBE FS sequence provides superior visualization of intra-articular structures, especially in sagital planes, and effectively reduce slice gap artifacts. However, it does not fully replace conventional sequence, especially in detecting edema and inflammation, in conclusion, the 3D SAGITAL PD CUBE FS Sequence is highly valuable as a complementary imaging technique in the diagnosis of knee injuries particularly ACL ruptures.